Assessment of the state of paravertebral muscles of the lumbar spine with help of computed tomography (Review of literature) - Radchenko, Volodymyr; Skidanov, Artem; Zmiyenko, Yuriy; Levitskaya, Liliya; Mischenko, Lyubov (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The article analyses a number of scientific publications about possibilities and results of study of paravertebral muscles with help of computed tomography. It is found out that computed tomography makes it possible to reveal the area of the transverse section of muscles and the extent of their X-ray attenuation in Hounsfield units, as well as to assess the distribution of tissues.